Influence of environmental conditions and aerobic fermentation time on the quality of coffee (Coffea arabica L.) var. Catucaí (Semiárida, 2024)
During the fermentation process, yeasts and bacteria break down the sugars that give coffee its unique flavor. Therefore, the purpose of this study was to determine if the aerobic fermentation time in two environmental conditions, specifically in pulped coffee beans of the Catucaí variety (Coffea arabica L.), has an effect on the quality of the cup coffee. To do this, variables such as the pH of the fermentation medium were studied, as well as the results obtained in beverage tastings. The main results show that ambient temperature affects fermentation conditions when it reaches 18.3 °C, causing a decrease in pH and therefore lactic fermentation. When analyzing the melting scores, it was found that the optimal fermentation time was achieved at 16 hours in a greenhouse environment with a value of 79.25, which is considered "good" according to the standards of the Specialty Coffee Association. Despite these treatments, the variety was not able to obtain a satisfactory result as a consequence of inadequate nutritional and phytosanitary management of the crop, which decreased the quality of the coffee drink, with scores lower than 80 points.
Keywords: acidity; benefit; cupping; temperature; pH